The norming of the "Evaluation du language Oral" and the prevalence of speech and language disorders in pre-school aged children from Yaoundé (Cameroon) - Tchoungui Oyono, Lilly (Division of Communication Sciences and Disorders, 2016)
Research suggests that speech and language disorders are among the most prevalent childhood disabilities in many countries. Identification and intervention for children with communication disorders are sought at an early stage, to avoid the consequences of untreated childhood speech and language problems that can lead to academic underachievement and even persist into adulthood. However, no study has been reported on the prevalence of speech and language disorders in the general population in Cameroon. Despite the published literature on the national burden of disease suggesting that a significant number of Cameroonian children might have limitations in their speech and language abilities. This descriptive cross-sectional study aimed to determine the prevalence of speech and language disorders, specifically, articulation, expressive language, receptive language, fluency and voice disorders; in a representative sample of French-speaking preschool children in Yaoundé, the capital city of Cameroon. A total of 460 children aged 3 to 5 years were recruited from the seven communes of Yaoundé city using multi-stage random sampling method. As there was no validated speech and language test available for the population of French-speaking preschool aged children in Cameroon, this study has contributed in its first part, to provide norms on three subtests of a standardised French speech and language test, the 'Evaluation du Langage Oral' (ELO) for this population. These norms can be used for clinical practice and research purpose in Cameroon. In order to determine the prevalence of articulation, expressive and receptive language disorders, a cut-off of two Standard Deviations (SD) below the normative mean was applied. The identification of fluency and voice disorders among participants was based on clinical judgement. All the assessments were performed by the researcher who is a qualified speech-language therapist with experience of practice in Cameroon. The findings indicated that the prevalence of articulation disorders was 3.6%, expressive language disorders was 1.3%, receptive language disorders was 3%, fluency disorders was 8.4% and voice disorders was 3.6%. The overall prevalence of speech disorders was 14.7%, language disorders 4.3% and speech and language disorders 17.1%. There was no significant difference in the prevalence of speech and language disorders according to gender. The prevalence of speech and language disorders in the present study was higher than that of many previous investigations conducted in other countries. The findings of this research reveals and emphasises the urgent need to build a strategy to develop speech and language services to serve the Cameroonian population.